The role of inflammatory factors in the tumor microenvironment of pancreatic cancer - Yuan, Yuzhang; Zhang, Haozhe; Wang, Zehua; Huang, Luying; Kabacaoglu, Derya; Zhang, Boxing; Song, Liang; Ai, Jiaoyu (Frontiers in Immunology, 2025)
Pancreatic cancer (PC) is an aggressive malignancy with a poor prognosis, and the tumor microenvironment (TME) plays a pivotal role in its initiation, progression, and response to treatment. Recent studies have highlighted the critical involvement of inflammatory factors in shaping and sustaining the PC microenvironment. Chronic inflammation is a hallmark of this cancer, with inflammatory molecules such as cytokines, chemokines, proteases, and other immune-modulatory factors driving tumor cell proliferation, metastasis, and resistance to therapy. These inflammatory factors exert their effects by modulating immune cell infiltration, extracellular matrix (ECM) remodeling, and angiogenesis. This review provides an overview of the diverse roles of inflammatory factors in the PC TME and explores their potential as therapeutic targets. It offers new perspectives for developing novel immunotherapies and inflammation-modulating strategies to improve the treatment of PC.